Pretending to be normal : living with asperger's syndrome (autism spectrum disorder) - Willey, Liane Holliday (Jessica Kingsley Publishers, 2015)
Compelling and witty, Liane Holliday Willey's account of growing to adulthood as an undiagnosed 'Aspie' has been read by thousands of people on and off the autism spectrum since it was first published in 1999. Bringing her story up to date, including her diagnosis as an adult, and reflecting on the changes in attitude over 15 years, this expanded edition will continue to entertain (and inform) all those who would like to know a little more about how it feels to spend your life 'pretending to be normal'.